1999
DOI: 10.1116/1.581968
|View full text |Cite
|
Sign up to set email alerts
|

Integration of fluorinated amorphous carbon as low-dielectric constant insulator: Effects of heating and deposition of tantalum nitride

Abstract: We investigated the effects of heating and deposition of tantalum nitride on fluorinated amorphous carbon (a-C:F) thin films, deposited by a cosputtering process using polytetrafluoroethylene and graphite targets. Carbon is observed by x-ray photoelectron spectroscopy (XPS) in four distinct chemical states, C–C, C–F, C–F2, C–F3, and the relative intensity of C–Fx to C–C increases with increasing fluorine content and decreasing deposition temperature. Heat treatment of this material in vacuum up to 450 °C resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…As expected, the fluorine content of the films increases as g/cm 3 and 1.6 g/cm 3 ± 0.2 g/cm 3 , which is lower than that of graphite, and attributed to the incorporation of fluorine [14], [37]. the results reported in references [38], [39], [40], [41]. …”
Section: Cf Psupporting
confidence: 79%
“…As expected, the fluorine content of the films increases as g/cm 3 and 1.6 g/cm 3 ± 0.2 g/cm 3 , which is lower than that of graphite, and attributed to the incorporation of fluorine [14], [37]. the results reported in references [38], [39], [40], [41]. …”
Section: Cf Psupporting
confidence: 79%
“…This interfacial Ta-F peak is observed at 684.8 eV in the F 1s spectra. 44 It has been reported previously that Ta-F bonding exists at 685.4 eV for Ta e-beam evaporated on AF-4 both before and after Ar-ion sputtering. 37 Also, this is the fingerprint of the parylene AF-4 monomer unit, CF 2 C 6 H 4 CF 2 + .…”
Section: Tan X Overlayersmentioning
confidence: 97%
“…Chang et al have shown the same interfacial chemistry for tantalum-nitride reactive sputtered onto fluorinatedamorphous carbon. 44 They show a significant loss of CF X bonding caused by the sputtering of the tantalum nitride and also evidence of significant Ta-F bonding at the interface. This interfacial Ta-F peak is observed at 684.8 eV in the F 1s spectra.…”
Section: Tan X Overlayersmentioning
confidence: 98%
“…Fluorinated amorphous carbon ( a -CF x ) films have been produced by plasma-enhanced chemical vapor deposition (PECVD), , inductively coupled plasma chemical vapor deposition (ICP−CVD), , magnetron sputtering deposition, and ion beam deposition. The deposition parameters that influence the properties of a -CF x films are known to include the carbon-to-fluorine elemental ratio in the film, the radio frequency power used in deposition, the process pressure, and the substrate temperature. ,, The composition of the gas mixture used to deposit the a -CF x film is known to influence the fluorine content in the film 28,37-41 and its deposition rate. ,,,,,,, Increasing the fluorocarbon-to-hydrocarbon ratio in the gas mixture increases both the fluorine content in the film and the deposition rate.…”
Section: Introductionmentioning
confidence: 99%
“…Fluorine incorporation into carbon films is known to significantly influence their tribological, mechanical, and structural properties. Increasing fluorine content leads to gradual reduction of the friction, adhesion, ,,, hardness, ,,,,,,,, stress, ,,, elastic modulus, , and density of the film. , A series of hardness tests, stress tests, and density measurements of a -CF x films revealed that the diamond-like structure of carbon films with very low fluorine content is transformed into a graphite-like structure and then a polymer-like structure as the fluorine content of the film is increased. ,,, X-ray photoelectron spectroscopy (XPS) analysis of a -CF x films further supports this model by revealing that the fraction of CF 2 and CF 3 groups increases as the fluorine content of the film increases. ,,,,, Raman spectra exhibit a gradual increase in the intensities of the D bands relative to those of the G bands as the fluorine content of the film increases, revealing the structural change of the film from a diamond-like to a graphite-like and then a polymer-like structure. ,,,,,, …”
Section: Introductionmentioning
confidence: 99%